TINJAUAN YURIDIS TINDAK PIDANA TANPA HAK MEMANIPULASI INFORMASI ELEKTRONIK SECARA BERSAMA-SAMA (STUDI PUTUSAN NO.359/PID.SUS/2021/PN JKT.SEL): Juridical Review Criminal Action Without The Right To Manipulate Electronic Information Collectively (Verdict Study No. 359/Pid.Sus/2021/PN Jkt.Sel) - Rizky Alfiantiko; Andi Widiatno (Universitas Trisakti, 2024)
In this era of globalization, data has become an important matter in one's identity where the data certainly has loopholes for people who want to take advantage in illegal ways, one of which is by manipulating electronic information. Manipulation of electronic information is a crime that enters the realm of cyber. The development of the digital world has led to new variations in committing crimes, one of which is related to concurrent regulations or Concursus Idealis. The legal basis for the crime of manipulating electronic information is regulated in Law Number 19 of 2016 concerning Electronic Information and Transactions. With the concomitant regulation of the crime of forgery of letters, this is the basis for the creation of this article using the Literature Study method, a type ofnormatif juridical research, with the nature of analytical descriptive research,and drawing conclusions using deductive logic. There are concurrent regulations carried out by actors in manipulating electronic information where the crime of forging letters is one part of the criminal act that is incorporated in it which is carried out in collaboration